Lessons from Covid-19 and the potential benefit of the implementation of Axon’s personal electronic health records (PEHR) into aesthetic care, plastic and reconstructive surgery - van Eeden; Samuel Jakobus; Ylihonko, Kristiina; Braidy, Nady; Kassas, Ahmad; Jakubetz, Hansjörg; Eeden, Wouter van; Békefi, Antal; Eeden, Walter van; Eeden, Werner van; Eeden, Zelda van; Taiwan, Jacob Lee; et al. (Springer Science and Business Media Deutschland GmbH, 2025)
Background: Covid-19 pandemic highlighted the need for implementing Personal Electronic Health Records (PEHR) for patients’ data management. Furthermore, this pandemic underscored the relevance for integrated and interoperable Electronic Health Records (EHR) to support disease surveillance, hospital capacity planning and resource management (Peek N, Sujan M, Scott P (2020) Digital health and care in pandemic times: impact of COVID-19. BMJ Health Care Inf 27(1):e100166. https://doi.org/10.1136/bmjhci-2020-100166). Due to the lack of comprehensive patients’ record in plastic, reconstructive and aesthetic surgery, Axon’s myHealth app offers a break-through patient-centric design allowing patients to be in control of their records and updating them in real-time for their plastic and aesthetic care providers to have a clearer understanding of patients’ history and progress from pre-op to post-op.
Methods: The Axon Dublin survey took place during Covid-19 pandemic in two phases: Phase 1 aimed to assess the feasibility of patients integrating the Axon myHealth application into their clinical visits. Testing occurred in a clinical environment, where patients were encouraged to download and use the Axon system with a health practitioner (HP) present. Phase 2 focused on home testing, evaluating patients’ willingness to manage their health remotely with HP assistance. This phase included self-testing activities such as performing rapid Covid-19 antigen tests, recording medical history, and measuring blood pressure at home.
Results: The Axon Dublin Study aimed to assess patient engagement, clinical impact, and cost-effectiveness of the Axon myHealth application. Over 85% of patients showed interest in owning a Personal Electronic Health Record. Notably, 36% continuously monitored chronic conditions. Clinical decisions, informed by patient data, saw 61.9% compliance. Noteworthy, 23% of hypertensive participants required immediate medication changes. Patient self-capture of data reduced consultation time. Public health implications were significant, with 39% vaccinated and 31% reporting complications. High user satisfaction (97%) demonstrated the app’s effectiveness in infection control and chronic care.
Conclusions: Offering patients the ability to update and control their data is a growing interest, with a clear need in plastic and aesthetic surgery to have a better understanding of a patient’s medical past and progress throughout the surgical process and period. This platform, which is time and cost efficient, can only facilitate personalised care and improve outcomes while maintaining patient’s confidentiality.
Level of evidence: Not gradable.